Near total and inorganic phosphorus concentrations as a proxy for identifying ancient activities in urban contexts: The example of dark earth in Brussels, Belgium. Issue 4 (10th December 2017) - Devos, Yannick
Abstract: Urban stratigraphy is characterized by complicated sequences resulting from many superimposed phases of human occupation and activity. Parts of these deposits are difficult to interpret solely based on field data. One typical example is "dark earth": thick, dark‐colored, humic, homogeneous archaeological deposits covering large areas. The correct interpretation of dark earths requires a geoarchaeological approach that involves detailed micromorphological observations. The present article discusses the potential of applying near total and inorganic phosphorus analyses as a quick and relatively cheap method to obtain a preliminary characterization of such urban deposits. For the town of Brussels (Belgium), a large database of 12 types of well‐identified urban deposits was created. Despite a series of postdepositional processes that affected most of these urban deposits, significant differences in near total (Pnt), inorganic (Pi), organic (Po) phosphate levels, and/or Pnt/Pi, Pni/Po ratios were observed in most types of deposits, thus enabling the rapid characterization of dark earth deposits.